Semrawangadh, Bhojpuri and Vidyapati: An Interwoven Identity - Thakur, Gopal (Nepalese Linguistics, 2025)
Semrawangadh or Simraungadh (officially) is a municipality in Bara district of the Madhesh state in Nepal. Literally it stands for a fort of simal trees, as it had been so, the capital city of Tirhut ruled by the Karnata dynasty kings from 1097 till1326 CE. Following defeat of King Harisingh Deva, the kingdom of Tirhut faced a chaos under power-tussle between the native kings and the Delhi sultans, and it ended with fall of Shiva Singh. Under his last command, Vidyapati took refuge in Benauli and composed his masterpieces of literature in Avahattha, his mother tongue in his own words. But the very place has been claimed to be Banauli in Saptari and his mother tongue Maithili, whereas, Vidyapati's Avahattha is Proto-Bhojpuri. Therefore, Semrawangadh, Bhojpuri and Vidyapati are parts of an interwoven identity. Historically and linguistically the article attempts to clarify it on the basis of qualitative and quantitative data.